PELATIHAN PENGEMBANGAN MEDIA AJAR BERBASIS ARTIFICIAL INTELLIGENCE MENGGUNAKAN APLIKASI GAMMA BAGI GURU DI KABUPATEN BARRU - Jamaluddin, Asham Bin; Pratiwi, Andi Citra; Azis, Andi Asmawati; Khalidatunnisa, Besse; Patongai, Dian Dwi Putri Ulan Sari (Universitas Negeri Makassar, 2025)
The use of digital technology based on Artificial Intelligence (AI) is now opening up significant opportunities to enhance the effectiveness and efficiency of learning. With the support of AI, teachers can create engaging, high-quality, and easy-to-understand learning media in a shorter time compared to using conventional digital tools. One AI-based application with great potential in educational media development is GAMMA. This application enables users to create visual media supported by well-structured, detailed, and informative content points. However, knowledge about GAMMA among teachers, particularly teachers in Barru Regency, is still limited. Therefore, this community service program aims to strengthen the capacity of teachers in developing AI-based instructional media. The program was carried out in three main stages: (1) presentation of materials on AI technology and the GAMMA application, (2) hands-on practice in developing instructional media using GAMMA, and (3) a discussion session to reflect on outcomes and challenges. Based on the evaluation results obtained through a questionnaire, the program successfully increased teachers’ knowledge and skills in using the GAMMA application to support more engaging and effective learning processes. In the future, teachers are expected to be better prepared to meet the challenges of 21st-century education.